Impact of international collaboration on dentistry related papers published in Kingdom of Saudi Arabia - Faisal Alonaizan; Soban Q Khan; Muhammad Ajmal Khan; Nadeem Siddique; Hend Alshammary; Marwah Alamoudi; Mohammed M. Gad; Jehan AlHumaid (Saudi Dental Journal)
Objective: This bibliographic analysis was designed to review all dental publications in the Kingdom of Saudi Arabia (KSA) and evaluate the effect of international collaboration on the impact of published articles. Methods: The Web of Science (WOS) database was used to extract all related published articles in the KSA from 1982 to 2021. The keywords were connected using Boolean Operators to download related articles. Downloaded articles were screened according to the following inclusion criteria: collaboration journal category, journal discipline, number of citations, number of authors, and impact factor. After applying the inclusion criteria and excluding single-author articles, 5,689 documents were included in the final analysis. The chi-square test and two-independent samples t-test were used to determine the statistical significance between the variables. Results: A significantly higher proportion of articles with international collaboration (51.4%) were published in dental journals than those published nationally (43.3%) or within the institutional level (41.8%) (P < 0.0001). In addition, the average number of citations (9.28 ± 23.8) ranged from 0 to 749, received by an article and the impact factor of the journal in which the article was published, significantly higher in the case of internationally collaborative work compared with national or within institutional collaboration (P < 0.0001). Conclusion: International collaboration positively affected the impact factor, number of citations, and quartile rank of published articles. Moreover, the number of co-authors in different countries contributes to the international collaboration effect.